Combinations of wet corn gluten feed and steam-flaked corn in finishing cattle diets: effects on acid-resistant E. Coli and coliforms, VFA Profiles and pH - J.J. Sindt; H. Thippareddi; D.L. Lambert; T.B. Farran; Sean P. Montgomery; H.J. LaBrune; James J. Higgins; James S. Drouillard; Randall K. Phebus (Kansas Agricultural Experiment Station Research Reports, 2001)
Finishing beef steers (615 head) were used in a 152-day experiment to evaluate the effects of feeding 80:0, 60:30 or 30:60 ratios (dry basis) of steam-flaked corn and wet corn gluten feed (WCGF, 30WCGF, 60WCGF) on acid-resistant E. coli and coliforms. On days 114 to 118 ruminal and fecal samples were collected from 180 steers and analyzed for pH, VFA, and total and acid-resistant Escherichia coli (E. coli) and coliforms. Ruminal (P=0.13) and fecal (P=0.10) VFA tended to decrease linearly as CGF increased. Consequently, there was a corresponding numerical linear increase in ruminal pH and a significant linear increase in fecal pH (P0.10) by dietary treatment.
Keywords: Cattlemen& #x27; s Day; 2001; Kansas Agricultural Experiment Station contribution; no. 01-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 873; Beef; E. coli; Food safety; Finishing cattle